Optimisation of genetic transformation procedure for watermelon (Citrullus lanatus Thumb.) - Thanh Nga, Nguyen Thi; Tuong, Ho Manh; Van, Pham Thi; Van, Nguyen Tuong; Ha, Chu Hoang; Binh, Le Tran (Academia Journal of Biology, 2012)
In this study, the binary vector pCB-gusplus carrying nptII and gus - intron genes as selectable and reportable markers was used to optimize Agrobacterium-mediated gene transformation protocol of four Vietnam watermelon lines. Agrobacterium tumefaciens CV58 habouring pCB-gusplus in the concentration of OD600 0.6-0.8 was infected into 5-7 day cotyledons for 30 minutes and co-cultured for 3 days. The transformed leave materials was cultured in the selectable medium containing MS salts and vitamins supplemented with 1.5 mg/l BAP, 0.5 mg/l IBA, 200 mg/l kanamycin và 500 mg/l cefotaxime. Regenerated shoots was rooted in MS medium added with 0.2 mg/l IBA, 100 mg/l kanamycin and 250 mg/l cefotaxime There was a significant difference in the transformation frequency among watermelon lines. F1 TG939 line showed the transformation frequency of 1.87%), following F9 Tieulong - Thanglong of 1.85%, F1 Kinhkong and F9 Binhthuan lines showed the transformation frequyency of 0%. The analysis of the obtained lines using GUS histochemical assay and PCR reaction with specific primers of ntpII gene had confirmed the presence of gus gene into 5 transgenic lines.